Less Than I Expected and oh so True? On the Interplay Between Expectations and Framing Effects in Judgments of Truth. (October 2019) - Jaffé, Mariela E.; Greifeneder, Rainer
This article investigates the negativity bias in truth judgments, which holds that negatively (vs. positively) framed statements are more likely to be judged true. Throughout four studies we find that expectations moderate the negativity bias. In particular, Study 1 failed to replicate the negativity bias with standard items. In Study 2 we investigated individuals' expectations regarding the statements. When systematically adjusting the percentages in negatively framed statements to be lower than expected, a negativity bias occurred in Study 3. Building on this knowledge in Study 4, we systematically decreased and increased percentages in both framing conditions, investigating the impact of under- versus overestimation. While expectations had no consistent effects for positive frames, overestimation (vs. underestimation) led to a higher likelihood of perceived truth in the negative framing condition. Results are discussed in context of current research on language and social psychology as well as post-truth politics.